God loves you [compact disc, unabridged] : he always has, he always will - Jeremiah, David, 1941- (Hachette Audio, 2012)
Dr. David Jeremiah reveals that not fully understanding and appreciating every critical dimension of God's love can lead to missed opportunities to experience His love. He explains how even the so-called negative dimension of God's actions--hell, prohibitive commandments, pain, and suffering in the world--can only be rightly understood by viewing them in light of God's true love.